Implementing PQRST Strategy To Improve Students’ Reading Comprehension At The Tenth Grade Of SMA Negeri 13 Maluku Barat Daya - Laka, Fransika S; Lekawael, Rosina F. J.; Nikijuluw, Renata C. G. V. (Koli Journal : English Language Education, 2022)
This research aimed to learn how to implement the “PQRST Strategy” in English class successfully and to find out the responses of the tenth-grade students of SMA NEG 13 MBD toward implementing the PQRST strategy in English class. This study was action research and covered two cycles. Generally, both cycles consist of planning, acting, observing, and reflecting. In collecting the data, this study used quantitative and qualitative methods. The qualitative is related to the observation checklist and questionnaire. The qualitative data were acquired from the pre-test and post-test. The result of the research showed the PQRST strategy has an important role in increasing students’ reading comprehension in the tenth grade of SMA NEG 13 MBD. It can be said that this strategy was easier and helped students in the teaching-learning process of the English class activity. It could be proved by raising the students’ reading comprehension test scores. The average score on the pre-test was 16,87; on the post-test, it was 63,67, which became 77,91. The PQRST strategy in reading (narrative text) could increase students’ reading comprehension skills. Based on the results of the discussion above, it can be concluded that applying the PQRST strategy to the tenth-grade students could be improved. On the other hand, this strategy was effective and an alternative way for the students, even the local teacher, to add their strategy to the teaching-learning process because it interested students in learning and remembering what they learned. It could also be seen from the result after cycle I, which was 43,75%, and then cycle II, where 84,37% of students achieved KKM